ANALISA RELASIONAL SYARI’AH DAN NEGARA - Fatmawati, Fatmawati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2010)
Shariah in the country and there is a very close relationship and can not be separated in the framework of the implementation and enforcement of Islamic law for the benefit of mankind in this atmosphere of state and nation. It will also mean that the goal of reduction in the Islamic Shariah is not solely for the implementation of the rituals of worship per se, but more than that is a legal instrument which should be obeyed in the life of the country to regulate the system of government. Shariah as the legal system, has set the basics, norms, ethics, values. And for its development based on dynamic and development of the human life handed over to the Muslims to manage and develop without abandoning the spirit of the shari'ah.